ILLOCUTIONARY ACTS IN WEBTOON “THE MASKED FABLES SEASON 1” - Devi Ayuningtyas; Senowarsito, Senowarsito; Dias Andris Susanto (JOEL: Journal of Educational and Language Research, 2023)
This research is aimed to find out the kinds of illocutionary acts, find out the most dominant illocutionary act, and find out the contribution of illocutionary act in Webtoon “The Masked Fables Season 1” to apllied pragmatic in teaching English. The source of data to support all the analysis for this research was taken from the Webtoon entitled ‘The Masked Fables Season 1’. The method used in this research is descriptive qualitative research for analyzing data. To analyze the utterances the researcher used Searle’s theory. From the result, the researcher found four types of illocutionary act such as representative (483 utterances), directive (330 utterances), commissive (169 utterances) and expressive (37 utterances). The most dominant type used in The Masked Fables Season 1 is representative. This research can be used for students' references for learning pragmatics, especially illocutionary acts. From this research, the students can find many types of illocutionary acts found in the Webtoon “The Masked Fables Season 1”. The scenario in this research can enrich students’ knowledge about illocutionary acts and it can increase students’ vocabulary and speaking skills.